(untitled) (Jurnal Neraca: Jurnal Pendidikan dan Ilmu Ekonomi Akuntansi, 2019)
Based on the preliminary observations that researchers have done at Abab 1 Public High School, that learning media conducted using conventional learning methods using conventional learning methods has been going well but has not got maximum results, this can be seen from the 65% completeness and those who have completed 35% of the KKM 75 that had been determined by the school. The formulation of the problem in this study is "Is There Any Effect of Application of Image Media on Student Learning Outcomes in Economic Subjects in Abab N 1 High School 2018/2019 Academic Year". The purpose of this study is to find out whether there is an effect of the application of image media on student learning outcomes in economic subjects at Abab N 1 High School 2018/2019 Academic Year. The method used is quasi-experimental research (quasi-experiment). The results of the study are based on the results of the hypothesis carried out using the t test while the regression formula that is used is a simple linear regression dummy variable, there is the influence of the application of image media on student learning outcomes on economic subjects in Abab 1 Public High School 2018/2019. This can be seen from the results of the hypothesis that obtained tcount 4.766> t table 1.996, then reject Ho accepted Ha means it can be concluded that there is influence of media images on student learning outcomes in Abab 1 Public High School 2018/2019 Academic Year, with the influence of 25.88% on the criteria low, while the remaining 74.12% is influenced by other factors.